2019
DOI: 10.1177/1203475419882647
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Assessment and Management of Pediatric Patients With Atopic Dermatitis: A Consensus Document. Section III: Treatment Options for Pediatric Atopic Dermatitis

Abstract: Because atopic dermatitis (AD) is a chronic, relapsing disease, treatment requires the use of both active therapy to control flares and preventative maintenance therapy to promote integrity of the skin barrier. In this third of four sections, important clinical considerations for the treatment of pediatric AD are reviewed. Emerging therapies in development for pediatric AD are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 93 publications
0
21
0
9
Order By: Relevance
“…Consensus: 100% (Voting Result*: 8,4,0,0,0) *Voting results reflect number of authors voting Strongly Agree, Agree, Neither Agree nor Disagree, Disagree, or Strongly Disagree, respectively. This expert panel agreed on highlighting the chronic inflammatory nature of AD, with pruritus noted as a major diagnostic criterion. HCPs should help patients and caregivers understand that AD is a recurrent and relapsing condition, and although the disease may go into periods of remission, it is important to be proactive about management in order to minimize future flares.…”
Section: Overview and Assessment Of Pediatric Admentioning
confidence: 99%
See 2 more Smart Citations
“…Consensus: 100% (Voting Result*: 8,4,0,0,0) *Voting results reflect number of authors voting Strongly Agree, Agree, Neither Agree nor Disagree, Disagree, or Strongly Disagree, respectively. This expert panel agreed on highlighting the chronic inflammatory nature of AD, with pruritus noted as a major diagnostic criterion. HCPs should help patients and caregivers understand that AD is a recurrent and relapsing condition, and although the disease may go into periods of remission, it is important to be proactive about management in order to minimize future flares.…”
Section: Overview and Assessment Of Pediatric Admentioning
confidence: 99%
“…These manuscripts may be consulted for a summary of the literature considered by our group. [2][3][4] Experts reviewed and aligned on the draft manuscript content at a meeting held in Toronto, Canada on May 11, 2019. At this meeting, a summary of the literature was presented by the authors, and the panel voted on 18 initial consensus statements based on the three identified topic areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biologic systemic therapies for moderate-tosevere AD are currently limited to dupilumab, which blocks the intercellular signaling of interleukin-4 (IL-4) and interleukin-13 (IL-13). However, other new therapies in the late-phase of drug development, such as the Janus kinase inhibitors (JAKi) abrocitinib, baricitinib, and upadacitinib, are broadening the systemic therapy repertoire [15,18]. The panel of experts showed a strong consensus (82% agreement) on the significant potential of JAKi for the treatment of moderate-to-severe AD in the near future.…”
Section: Treatmentmentioning
confidence: 99%
“…Additionally, it may occasionally be necessary to complement maintenance therapy with treatment for acute flares and-in the most severe cases-systemic treatment. In the past few years, the development of new drugs for pharmaceutical treatment (including topical phosphodiesterase 4 inhibitors [15] and biological systemic treatments [14,16]) has broadened the therapeutic repertoire for AD. The increasing trend to use therapeutic tools may continue with the emergence of systemic drugs targeting alternative steps in the atopic signaling pathway, such as Janus kinase inhibitors [17,18].…”
Section: Introductionmentioning
confidence: 99%